COMP Report: CPQR technical quality control guidelines for CyberKnife® Technology. (26th January 2018) - Vandervoort, Eric; Patrocinio, Horacio; Chow, Tom; Soisson, Emilie; Nadeau, Dominic Béliveau
Abstract: The Canadian Organization of Medical Physicists (COMP), in close partnership with the Canadian Partnership for Quality Radiotherapy (CPQR) has developed a series of Technical Quality Control (TQC) guidelines for radiation treatment equipment. These guidelines outline the performance objectives that equipment should meet in order to ensure an acceptable level of radiation treatment quality. This particular TQC contains detailed performance objectives and safety criteria for CyberKnife ® Technology. The quality control recommendations in this document are based upon previously published guidelines and the collective experience of all Canadian sites using this technology. This TQC guideline has been field tested at the newest Canadian CyberKnife installation site and includes recommendations for quality control of the Iris™ and InCise™ MLC collimation systems.